1995
DOI: 10.1109/68.384526
|View full text |Cite
|
Sign up to set email alerts
|

Monolithic optoelectronic circuit design and fabrication by epitaxial growth on commercial VLSI GaAs MESFET's

Abstract: Abshct-A technique for realizing large-scale monolithic OEIC's, which involves epitaxially growing GaAs-based heterostructures on fully metallized commercial VLSI GaAs MES-FET integrated circuits, has recently been reported. In the initial work the circuits and LED's occupied distinct halves of a chip, the dielectric growth window was wet-etched after circuit fabrication, and the LED's required both n and p ohmic contacts to be formed after epitaxial growth. In this letter we report the use of standard foundry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Using a commercial GaAs-based MESFET process, it has been shown that heterostructures may be grown on the fully processed integrated circuits [97]; LEDs and simple optical functionality have been demonstrated. Alternatively, III±V semiconductor-based components may be hybridly bonded to CMOS driver electronics [98].…”
Section: Optics Integrated With Electronicsmentioning
confidence: 99%
“…Using a commercial GaAs-based MESFET process, it has been shown that heterostructures may be grown on the fully processed integrated circuits [97]; LEDs and simple optical functionality have been demonstrated. Alternatively, III±V semiconductor-based components may be hybridly bonded to CMOS driver electronics [98].…”
Section: Optics Integrated With Electronicsmentioning
confidence: 99%
“…The OPTO-CHIP project is summarized in Sec. 4. Basic device and circuit characteristics and a number of optoelectronic integrated circuit results are presented in Sec.…”
Section: Introductionmentioning
confidence: 99%
“…Work on EoE began [1][2][3][4][5][6][7][8][9][10][11][12][13][14] at the Massachusetts Institute of Technology ͑MIT͒ in 1990. Initial results included the fabrication of LED-based neural-network optoelectronic integrated circuits 4 ͑OEICs͒ as well as the integration of resonant tunneling diodes 7 ͑RTDs͒ and surface-normal multiple-quantum-well modulators 8 ͓also known as selfelectro-optic devices ͑SEEDs͔͒. The performance of this early work was limited by a number of process shortcomings that recent innovations have overcome.…”
Section: Introductionmentioning
confidence: 99%
“…SEED circuits were designed and fabricated as multiproject chips which include SEED receivers, transmitters, NOR gates, and other functional logic [9]. In addition, a 10 x 10 SEED optical "bump circuit" neuron array was designed [6].…”
Section: B Eoe-seed Design and Reduced-temperature Growthmentioning
confidence: 99%
“…The growth regions for modulators, called dielectric growth wells (DGW's), are allocated during design and opened during fabrication. Once the circuitry is fully fabricated by Vitesse through MOSIS [9], the MQW modulator structures are grown by molecular beam epitaxy (MBE) in the cleaned DGW's. Post-growth fabrication turns the heterostructures into SEED's and interconnects them with the electronics on the same chip to form the final monolithic OEIC.…”
Section: Introduction Ultiple-quantum-well (Mqw) Modulatorsmentioning
confidence: 99%